2011
DOI: 10.1097/mcg.0b013e3181f39f4e
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Preventive Endoscopic Balloon Dilation for Esophageal Stricture After Endoscopic Resection

Abstract: Preventive EBD is an effective procedure to prevent postEMR/ESD stricture. Preventive EBD should be considered when EMR/ESD results in a mucosal defect with a circumference greater than three-fourths of the esophageal lumen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 19 publications
4
148
2
1
Order By: Relevance
“…Risk of stricture after near circumferential ESD could be as high as 100%. Numerous preventive strategies have been proposed, including the use of topical or systemic anti-inflammatory agents, prophylactic endoscopic balloon dilation and tissue engineering approaches (42)(43)(44)(45)(46). Unfortunately, the efficacy of these strategies is not well established, and there is currently a lack of standardized approach in prevention of this potentially debilitating complication.…”
Section: Outcomes Of Endoscopic Resection Of Early Esophageal Cancersmentioning
confidence: 99%
“…Risk of stricture after near circumferential ESD could be as high as 100%. Numerous preventive strategies have been proposed, including the use of topical or systemic anti-inflammatory agents, prophylactic endoscopic balloon dilation and tissue engineering approaches (42)(43)(44)(45)(46). Unfortunately, the efficacy of these strategies is not well established, and there is currently a lack of standardized approach in prevention of this potentially debilitating complication.…”
Section: Outcomes Of Endoscopic Resection Of Early Esophageal Cancersmentioning
confidence: 99%
“…The longitudinal length of mucosal defect over 30 mm was also risk factor of severe stricture. 3 Some new methods against post-ESD stricture were developed and reported such as planned EBD dilatation, local TA injection, and oral prednisolone administration. Dysphagia in association with recurrent stenosis was seen in 13.6% in the pre-emptive EBD but in only 6.3% in the oral prednisolone.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have demonstrated the effectiveness of the local injection or oral administration of steroids for preventing strictures of esophagus and deformity of stomach 1 with sufficient advantage of their anti-inflammatory and fibroblast inhibitory effects, strictures still occur, and additional endoscopic balloon dilatation (EBD) is required in cases of circumferential esophageal resection. 2,3 In addition, local steroid injection also increases the risk of bleeding following puncture. The oral administration of steroids to diabetic patients can also cause impaired glycemic control.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Ezoe, dkk. 24 dilatasi esofagus dengan balon juga bermanfaat untuk mencegah terjadinya striktur esofagus setelah reseksi mukosa perendoskopik untuk kanker esofagus. Menurut Hashimoto, dkk.…”
Section: Terapi Endoskopik Untuk Reseksi/diseksi Mukosa Esofagusunclassified